The shape of inner space : string theory and the geometry of the universe's hidden dimensions - Yau, Shing-Tung, 1949-; Nadis, Steven J. (New York : Basic Books, 2010)
String theory says we live in a ten-dimensional universe, but that only four are accessible to our everyday senses. According to theorists, the missing six are curled up in bizarre structures known as Calabi-Yau manifolds. Here, Shing-Tung Yau, the man who mathematically proved that these manifolds exist, argues that not only is geometry fundamental to string theory, it is also fundamental to the very nature of our universe. Time and again, where Yau has gone, physics has followed. Now for the first time, readers will follow Yau's penetrating thinking on where we've been, and where mathematics will take us next. A fascinating exploration of a world we are only just beginning to grasp, The Shape of Inner Space will change the way we consider the universe on both its grandest and smallest scales.--From publisher description.
'Space/time' (poem) -- The shapes of things to come -- A universe in the margins -- Geometry in the natural order -- A new kind of hammer -- Too good to be true -- Proving Calabi -- The DNA of string theory -- Through the looking glass -- Kinks in spacetime -- Back to the real world -- Beyond Calabi-Yau -- The universe unravels -- The search for extra dimensions -- Truth, beauty, and mathematics -- The end of geometry? -- Another day, another donut -- Entering the sanctum --'A flash in the middle of a long night' (poem).
Includes bibliographical references (p. 331-343) and index.
Keywords: Hyperspace; String models; Fourth dimension